(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The International Accounting Rules (NIC), are the result of the current accounting harmonization produced by the global economic environment. Its principal objective is to reflect the accurate financial & wealth situation of the company.They include two new significant issues; the first one is the concept of the fair value of the assets and the second, the company’s freedom to choose the accounting policies to be established. These contents should be studied in depth in order to adjust the financial statements to the company’s strategy.